SIMPLIFYING COMPLEX IMAGE REPRESENTATION: EASY SOLUTIONS FOR PENCIL DRAWINGS - Sharabaev Ulugbek Mukhamedovich (Galaxy International Interdisciplinary Research Journal, 2023)
Creating pencil drawings of complex images can be a challenging task for artists, especially those who are new to the medium. This scientific article explores various easy solutions and techniques that simplify the process of rendering complex images with pencils. It delves into methods such as breaking down the subject into basic shapes, utilizing shading and hatching techniques, employing reference grids, and leveraging the power of erasing and smudging. By employing these accessible strategies, artists can achieve remarkable results in their pencil drawings while navigating the intricacies of complex subjects.